The Second Wave of Attention Economics. Attention as a Universal Symbolic Currency on Social Media and beyond - Heitmayer, Maxi (Interacting with computers, 2025)
Abstract Since the advent of social media, capturing and holding the attention of people has become paramount for the success of products, political messages and even research. The economics of attention is often seen as part of the market economy. We argue that a larger societal transformation is underway, which will see attention become the defining currency that moves individuals, exchanges, and many other elements of society. This paper connects the attention economy to the institutional foundations of modernity. It then discusses how attention can be accumulated and exchanged like a currency and proposes a dual-stream model distinguishing between calcified and flow attention. Based on this model, we investigate recent developments facilitating the use of attention as a currency, and their potential impact on our daily lives more generally. We conclude by providing an outlook and concrete questions for future research to understand where the economics of attention economy is heading.